2005
DOI: 10.1021/ie0503803
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis on the Growth of Negative Ions in Pulse-Modulated SiH4 Plasmas

Abstract: The evolutions of chemical species (SiH4, SiH x , SiH x +, and polymerized negative ions) in the pulse-modulated SiH4 plasmas during the plasma-on and -off times were analyzed by solving the model equations of chemical species. During the plasma-on time, the SiH x concentration increases with time, mainly by the generation reaction from SiH4, but during the plasma-off time, it decreases because of the reaction with H2. During the plasma-on time, the concentrations of negative ions increase with time by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
(172 reference statements)
0
14
0
Order By: Relevance
“…Recent developments in mass-spectral sampling technique have brought forward new evidence on the role of negative ions and cluster formation in pulsed plasma polymerisation systems22, 35, 36. These investigations have clearly shown the presence of cluster ions ranging up to multiple monomer mass units generated by ion-neutral chemistry in gas phase predominantly occurring in the plasma off-period 35, 36. In light of these reports, we extended the study to explore the effects of varying the OFF-time in an attempt to explore the optimal t on / t off ratios to maximise the functional group retention for maleic anhydride plasma polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in mass-spectral sampling technique have brought forward new evidence on the role of negative ions and cluster formation in pulsed plasma polymerisation systems22, 35, 36. These investigations have clearly shown the presence of cluster ions ranging up to multiple monomer mass units generated by ion-neutral chemistry in gas phase predominantly occurring in the plasma off-period 35, 36. In light of these reports, we extended the study to explore the effects of varying the OFF-time in an attempt to explore the optimal t on / t off ratios to maximise the functional group retention for maleic anhydride plasma polymers.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Low-temperature plasmas are generated by an inductively coupled rf plasma process with a spiral-shape electrode installed around the reactor. The plasma reactor rotates with a rotation speed, R , to deposit uniformly the precursors of TiO 2 thin films onto the surface of glass beads.…”
Section: Theorymentioning
confidence: 99%
“…with aluminum oxide film to increase the chemical stability of the SiC particles. Kim et al [10][11][12] proposed a rotating cylindrical PCVD reactor for uniform particle coating with amorphous Si (a-Si) and suggested that the rotating PCVD reactor could be used to provide thin films on the particles with higher quality of a-Si, as compared with other particle-coating processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to make a large size product material. In addition, special techniques are needed to manage the reactants in the sol-gel process [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%